PI3K/AKT/mTOR pathway, hypoxia, and glucose metabolism: Potential targets to overcome radioresistance in small cell lung cancer - Huan Deng; Yamei Chen; Peijing Li; Qingqing Hang; Peng Zhang; Ying Jin; Ming Chen (Cancer Pathogenesis and Therapy, 2023)
Small cell lung cancer (SCLC) is a highly aggressive tumor type for which limited therapeutic progress has been made. Platinum-based chemotherapy with or without thoracic radiotherapy remains the backbone of treatment, but most patients with SCLC acquire therapeutic resistance. Given the need for more effective therapies, better elucidation of the molecular pathogenesis of SCLC is imperative. The phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway is frequently activated in SCLC and strongly associated with resistance to ionizing radiation in many solid tumors. This pathway is an important regulator of cancer cell glucose metabolism, and its activation probably effects radioresistance by influencing bioenergetic processes in SCLC. Glucose metabolism has three main branches—aerobic glycolysis, oxidative phosphorylation, and the pentose phosphate pathway—involved in radioresistance. The interaction between the PI3K/AKT/mTOR pathway and glucose metabolism is largely mediated by hypoxia-inducible factor 1 (HIF-1) signaling. The PI3K/AKT/mTOR pathway also influences glucose metabolism through other mechanisms to participate in radioresistance, including inhibiting the ubiquitination of rate-limiting enzymes of the pentose phosphate pathway. This review summarizes our understanding of links among the PI3K/AKT/mTOR pathway, hypoxia, and glucose metabolism in SCLC radioresistance and highlights promising research directions to promote cancer cell death and improve the clinical outcome of patients with this devastating disease.